Hemophagocytic lymphohistiocytosis in an adult kidney transplant recipient successfully treated by plasmapheresis: a case report and review of the literature - Nußhag, Christian; Morath, Christian; Zeier, Martin; Weigand, Markus A.; Merle, Uta; Brenner, Thorsten (Medicine, 2017)
Rationale: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening disease entity primarily described in children, but not less relevant in adults. It is characterized by a misdirected activation of the immune system, resulting in an uncontrolled cytokine release from macrophages and cytotoxic T-cells (CTLs). Primary HLH relies on a genetic predisposition, whereas secondary HLH develops in the context of infections, malignancies or autoimmune diseases. However, the awareness and therapeutic knowledge for HLH in adulthood is limited. Most therapy protocols are almost exclusively validated in pediatric cohorts and for primary HLH. Their transferability to adult individuals with mostly secondary HLH is doubtful. Especially the high liver and bone marrow toxicity of applied etoposide-based protocols is discussed controversially and connected to overwhelming infections and death. Patient concern: A 51-year old, male, kidney transplant recipient was admitted to our center suffering from diarrhea, fever, nausea, hyponatremia, kidney graft failure, disorientation, progressive hemodynamic instability, and multiorgan failure. Diagnoses: Clinical and laboratory findings resembled those of a septic shock. Ferritin and soluble interleukin-2 receptor (sCD25) levels were disproportionally elevated. Only a mild hepatosplenomegaly was diagnosed in a CT scan. A T2-weighted, fluid-attenuated inversion recovery MRI showed marked, bilateral and periventricular white matter hyperintensities. The cerebrospinal fluid (CSF) analysis showed a moderately elevated protein content and cell count. There was no evidence of any bacterial, viral, or parasitic infection. The diagnosis of HLH was made. Interventions & Outcomes: The patient was successfully treated by a combined approach consisting of plasma exchange (PE), corticosteroids, anakinra, and cyclosporine (CsA). Lessons: HLH is an important differential diagnosis in critically ill patients. Its unspecific clinical picture complicates an early diagnosis and may be misclassified as sepsis. A combination of plasma exchange (PE), corticosteroids, anakinra, and cyclosporine (CsA) may be a promising and less toxic approach for HLH therapy in adults.